Women and homestay in Sayan village, Bali: Roles, challenges, and contributions toward sustainable development goals (SDGs) - Pertiwi, Putu Ratih; Sulistyawati, Agung Sri; Sari, Ni Putu Ratna (Journal of Commerce, Management, and Tourism Studies, 2025)
This study explores the gendered dynamics of community-based tourism through the participation of women in homestay management in Sayan Village, Ubud, Bali. Guided by an interpretive-constructivist paradigm, the research employed a qualitative approach using in-depth interviews, participatory observation, and document analysis to understand women’s roles, challenges, and empowerment processes in local tourism. The findings reveal that women play multifaceted roles as homemakers, cultural mediators, and informal managers who sustain both household economies and the social identity of the community. However, their participation remains limited by structural and cultural barriers such as unequal access to capital, domestic workloads, and underrepresentation in decision-making. Despite these constraints, women demonstrate agency through everyday negotiation, quiet leadership, and solidarity among fellow homestay owners. The study highlights that empowerment in tourism is not a linear progression but a negotiated process shaped by local values of ngayah (service) and Tri Hita Karana (harmony). Homestays in Sayan thus function as gendered spaces of negotiation where cultural obligations and economic aspirations intersect. These findings contribute to broader theoretical discussions on gendered sustainability and provide practical insights for gender-sensitive tourism policies. Ultimately, women’s participation in homestay tourism aligns with the goals of SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), and SDG 11 (Sustainable Communities).